The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/jmor.20403
|View full text |Cite
|
Sign up to set email alerts
|

The interbranchial lymphoid tissue of Atlantic Salmon (Salmo salarL) extends as a diffuse mucosal lymphoid tissue throughout the trailing edge of the gill filament

Abstract: The teleost gill forms an extensive, semipermeable barrier that must tolerate intimate contact with the surrounding environment and be able to protect the body from external pathogens. The recent discovery of the interbranchial lymphoid tissue (ILT) has initiated an anatomical and functional investigation of the lymphoid tissue of the salmonid gill. In this article, sectioning of gill arches in all three primary planes revealed an elongation of the ILT outward along the trailing edge of the primary filament to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Furthermore, the gill contained the most intense concentration of T-cell activity outside of the thymus, with elevated expression of T-cell associated genes such as cd8a and foxp3b , and expression of these genes was seasonal in the gill but non-seasonal in the thymus. These observations are consistent with the known responsiveness of immune gene expression in the teleost gill to environmental stimuli [ 50 ], and also with the recent discovery and characterization of extensive, T-cell rich, interbranchial lymphoid tissue (ILT) in teleost fishes [ 12 , 51 53 ]. Our results suggest the possibility that ILT may have an important role in seasonal immune function.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the gill contained the most intense concentration of T-cell activity outside of the thymus, with elevated expression of T-cell associated genes such as cd8a and foxp3b , and expression of these genes was seasonal in the gill but non-seasonal in the thymus. These observations are consistent with the known responsiveness of immune gene expression in the teleost gill to environmental stimuli [ 50 ], and also with the recent discovery and characterization of extensive, T-cell rich, interbranchial lymphoid tissue (ILT) in teleost fishes [ 12 , 51 53 ]. Our results suggest the possibility that ILT may have an important role in seasonal immune function.…”
Section: Discussionsupporting
confidence: 86%
“…3). This finding coincides well with the report by Dalum et al (2015) who found higher expression of CD4-1 genes than CD8α genes in all gill segments investigated. Interestingly, the higher proportion of CD4-1 + T cells in the gill is in large contrast with the intestine where percentages of CD8α + T cells tend to be higher than that of CD4-1 + T cells.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the teleost interbranchial lymphoid tissue (ILT) was initially proposed as a possible exception that could represent an organized structure of teleost MALT (Aas et al, 2014; Gómez et al, 2013; Koppang et al, 2010; Salinas et al, 2011), however, this notionwas reexamined and recently the ILT has been classified as a diffuse lymphoid tissue (Dalum et al, 2015). Importantly, it has been established that PP are not absolutely necessary for IgA production in mice (Lorenz and Newberry, 2004; Tsuji et al, 2008) which occurs also extrafollicularly.…”
Section: The Anatomy Of the Intestinal Immune Systemmentioning
confidence: 99%